2022
DOI: 10.1002/vrc2.273
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial effusion in a central bearded dragon (Pogona vitticeps), with a technique for pericardiocentesis

Abstract: A 10‐year‐old central bearded dragon (Pogona vitticeps) presented with dyspnoea, tachypnoea, lethargy, pale mucous membranes, excessive oral mucus and exercise intolerance. Echocardiography demonstrated a marked pericardial effusion. A pericardiocentesis was performed under general anaesthesia, demonstrating cytology consistent with a presumptive diagnosis of a proteinaceous effusion secondary to atherosclerosis. Nonspecific abnormalities were diagnosed on haematology and biochemistry, including a heterophilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…7,21,32,42 Ultrasound examination of reptiles and amphibians are frequently conducted under chemical or physical restraint. 2-4,6-8,13,21,27, 30,32,33,37,41,42 In this study, the ultrasonographic appearance of major coelomic organs was reported in conscious, unrestrained axolotls in ventral recumbency, thereby lessening the possible effects of stress, sedation, and physical compression of the coelomic organs. 7,27,41 All major coelomic organs could be identified using this method, although the intestinal loops were difficult to assess, and pancreas and adrenal glands were not located.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,21,32,42 Ultrasound examination of reptiles and amphibians are frequently conducted under chemical or physical restraint. 2-4,6-8,13,21,27, 30,32,33,37,41,42 In this study, the ultrasonographic appearance of major coelomic organs was reported in conscious, unrestrained axolotls in ventral recumbency, thereby lessening the possible effects of stress, sedation, and physical compression of the coelomic organs. 7,27,41 All major coelomic organs could be identified using this method, although the intestinal loops were difficult to assess, and pancreas and adrenal glands were not located.…”
Section: Discussionmentioning
confidence: 99%
“…44 In reptiles, pericardial effusion was initially considered an indicator of cardiac disease but is now increasingly documented as incidental in some species. 7,21,32,42…”
Section: Discussionmentioning
confidence: 99%